An improved time over threshold method using bipolar signals. (25th June 2018) - Jung, Jiwoong; Choi, Yong; Kim, Kyu bom; Lee, Sangwon; Choe, Hyeok-jun
Abstract: The time over threshold (TOT) method has been recently proposed as a signal processing method used to calculate time and energy information by measuring the pulse arrival time and pulse duration over a preset threshold. Although TOT has been reported as an effective method for front end readout in PET applications, it has several limitations, including its non-linearity, lower dynamic range, and a trade-off between energy resolution and coincidence resolving time (CRT). In this study, we propose a novel design we developed to improve performance with regard to these problems occurring in the conventional TOT by employing a bipolar signal and two comparators. Using a high frequency CR shaping filter, a detected signal was converted into a bipolar signal, and the positive pulse of the converted bipolar signal had a fast rising time, while the negative pulse had a linear slope. The bipolar TOT circuit was composed of a preamplifier, a CR shaping filter, and two comparators. The PET detector was composed of a single LYSO coupled with 4  ×  4 SiPM arrays, a bipolar TOT circuit, and an FPGA based TDC. And this was constructed to evaluate the performance of the proposed bipolar TOT method. A 16-ch PET detector module consisting of a 4  ×  4 array LYSO coupled to a 4  ×  4 SiPM arrays, an Anger logic discretized positioning circuit, and a 4-ch bipolar TOT circuit was also constructed to evaluate the functionality of the bipolar TOT method for PET applications. The pulse height resolution and CRT were measured using both the bipolar TOT method and the conventional TOT method. While the bipolar TOT method provided a similar pulse height resolution (10.4%  ±  0.1%), the integral non-linearity (1.4%) and CRT (168  ±  4 ps) measured using the bipolar TOT method were greatly improved compared to those (17.2% and 258  ±  15 ps, respectively) measured with the conventional TOT method. The positions of the crystals were clearly identified, as seen in the flood histogram acquired using the 4-ch bipolar TOT circuit. The measured average pulse height resolution and average CRT for the 16-ch detector module were 11.5%  ±  0.2% and 516  ±  24 ps. The results obtained in this study indicate that the bipolar TOT method requiring a relatively small number of electronic components could effectively improve the CRT, linearity and dynamic range. Furthermore, they also demonstrated the extendibility allowing the development of a PET system that consists of a large number of detectors.